POLA PERTUMBUHAN KERANG MUTIARA Pinctada margaritifera DI PERAIRAN SULAWESI UTARA - Ockstan Kalesaran; Cyska Lumenta; Winda Mingkid (Universitas Mataram, 2021)
The pearl oyster Pinctada margaritifera (Linnaeus, 1758) or black lip pearl oyster is a marinebivalves with important economic value. This Indo-Pacific species is found in abundance in the waters of North Sulawesi, but cultivation activities have not been optimized. Growth information is important for aquaculture activities because it is a useful indicator to determine the health of pearl oysters and environmental suitability (Moussa, 2013). The purpose of this study was to determine the growth pattern of P. margaritifera pearl shells in the waters of North Sulawesi. Species P. margaritifera were collected at a depth of 2-20 m in the waters of North Minahasa Bahoi, Arakan waters South Minahasa and Talengen waters Sangihe Islands, North Sulawesi Province. The morphometric parameters observed included shell length (PC), shell height (TC), shell thickness (tC), and total weight (BT). The relationship between length, height, shell thickness and total weight was analyzed by regression equation. Morphometric measurements of P. margaritifera showed average shell length (PC) of 95.26 mm (Arakan waters), 81.15 mm (Talengen waters) and 70.19 mm (Bahoi waters). The growth pattern of P. margaritifera in the waters of Bahoi, Arakan and Talengen, North Sulawesi Province was allometric negative. This means that the increase in length, height and thickness of the shell is faster than the total weight.